Secretory structures in flourensia campestris and F. oolepis : ultrastructure, distribution, and (-)-Hamanasic acid A secretion - Silva, Mariana Paola (2015)
Fil: Silva, Mariana Paola. Universidad de Buenos Aires. Facultad de Agronomía. Sede Punilla. Córdoba, Argentina.